Prarancangan Pabrik Magnesium Sulfat dari Magnesium Karbonat dan Asam Sulfat Kapasitas 30.000 Ton Per Tahun - Amanah, Siti Nur; , Rois Fatoni, S.T., M.Sc, Ph.D sel (2017)
Preliminary design of magnesium sulphate plant aims to meet the requirement of magnesium carbonate in Indonesia. The plant with a capacity of 30,000 tons/year will be established in Gresik, East Java. Magnesium sulphate is used for conditioning agent wool and cotton in textile industry, mixed of cathartic and analgesic medicine in pharmacy industry. Raction formation of magnesium sulphate is just one step and decomposition with a total conversion of 90%. Reaction is conducted in continous stirred tank reactor at a temperature of 82ᵒC and a pressure of 1 atm in solid liquid phase condition. This process needs 2.015,9848 kg/h magnesium carbonate, 2.164,0857 kg/h sulphuric acid, 1.457,0876 kg/h water, and 141,2361 kg/h magnesium oxide. The supporting utility unit provides 1.639,2944 kg/h water which is supplied by Brantas river, 4.101,2003 kg/h saturated steam which is produced of boiler with 110,6033 liters/h. Pressure air is provides 71,064 m3/h and the demand for electricity and fuel oil are 150 kWh and 17,2 l/h, respectively. Magnesium sulphate plant is standed with area 14.763 m2 and 162 employees. Analysis economic conclude that percent Return On Investment (ROI) before and after tax are respectively 19.73% and 14.80%. Pay Out Time (POT) before and after tax requires sequently 3.02 and 3.66 years. Break Even Point (BEP) is roughly 52.99% and Shut Down Point (SDP) is 24.50%. Disccounted Cash Flow (DCF) is approximately 30.09%. Therefore, this calculation exhibits that establishmnet of magnesium sulphate plant is feasible.